Ultimate effect of non-identity of resistive elements of high-voltage arm on frequency characteristics of broadband voltage divider (analytical research) - Brzhezitsky, V. O.; Haran, Y. O.; Trotsenko, Y. O.; Protsenko, O. R.; Derzhuk, A. O.; Dixit, M. M. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Determination in the analytical form of the maximum limiting influence of the non-identity of the resistive elements of the high-voltage arm on the amplitude-frequency characteristic and phase-frequency characteristic of the voltage divider with parallel-series connection of R-, C-elements of the high-voltage arm. Methodology. Based on the previously developed theory of broadband voltage dividers with parallel-series connection of R-, C-elements, analytical expressions for amplitude-frequency and phase-frequency characteristics of the voltage divider are obtained and investigated taking into account the limit case of nonidentical resistive elements of high-voltage arm. Results. The nature of the dependencies of the frequency characteristics of the broadband voltage divider on the value of the tolerance of the resistive elements of the high-voltage arm, the division factor of the voltage divider in a wide range of frequency changes are determined. Simplified approximating expressions for the maximum values of frequency characteristics of the voltage divider are proposed and their error is determined. Originality. For the first time in the analytical form the limiting influence of non-identity of resistive elements of a high-voltage arm of a voltage divider on its frequency characteristics is considered. A mathematical model of this influence is constructed and the limit values of frequency characteristics of the voltage divider are determined. Practical value. It is recommended to introduce into the normative documentation of broadband voltage dividers the corrected value of the division factor, which allows to significantly reduce the deviation of the actual value of the division factor of the voltage divider from the normalized value in a wide range of frequency changes.

На основі раніше розвинутої теорії широкосмугових подільників напруги з паралельно-послідовним з’єднанням R-, C-елементів вперше одержані аналітичні вирази для амплітудно-частотної та фазо-частотної характеристик подільника напруги з урахуванням граничного випадку неідентичності резистивних елементів високовольтного плеча. Визначений загальний характер залежностей частотних характеристик від значення допуску резистивних елементів, коефіцієнта ділення подільника напруги в широкому діапазоні зміни частоти. Запропоновані спрощені апроксимуючі вирази для максимальних значень частотних характеристик та визначено їх похибки. Рекомендовано уведення в нормативно-технічну документацію широкосмугових подільників напруги відкоригованого значення коефіцієнта ділення.
Keywords: high-voltage divider; frequency characteristics; analytical expressions; tolerance of resistive elements; parameters adjustment; високовольтний подільник напруги; частотні характеристики; аналітичні вирази; допуск резистивних елементів; коригування параметрів